Charlie D. Hankin. Break and Flow: Hip-Hop Poetics in the Americas. New World Studies. Charlottesville: University of Virginia Press, 2023. x, 276 pp. (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2024)
Book Review..N/A